First-passage probabilities for randomly excited mechanical systems by a selective Monte-Carlo simulation method - Labou, M. (Український математичний журнал, 2004)
In this paper, Monte-Carlo methods used for the reliability assessment of structures under stochastic excitations are further advanced, e.g., by leading the generated samples towards the low probability range which is practically not assessable by direct Monte-Carlo methods. Based on criteria denoting the realizations that lead most likely to failure, a simulation technique called the “Russian Roulette and Splitting” (RR&S) is presented and discussed briefly. In a numerical example, the RR&S procedure is compared with the direct Monte-Carlo simulation method (MCS), demonstrating comparative accuracy. Продовжено модифікацію методів Монте-Карло для оцінки надійності структур при стохастичних збуреннях, а саме, згенероваиі виборки зводяться до множини значень невеликої ймовірності, що практично неможливо при застосуванні прямих методів Монте-Карло. На основі критеріїв визначення тих реалізацій, що скоріш за все закінчуються невдачею, описано і стисло проаналізовано метод моделювання „Російська рулетка та розщеплення". Наведено приклад, в якому метод „Російська рулетка та розщеплення" порівнюється з прямим методом моделювання Монте-Карло і визначається їх порівняльна точність.